Short-term and long-term effect of non-pharmacotherapy for adults with ADHD: a systematic review and network meta-analysis - Yang, Xinyue; Zhang, Lin; Yu, Jing; Wang, Meng (Frontiers in Psychiatry, 2025)
BackgroundAttention-Deficit/Hyperactivity Disorder (ADHD) is a lifelong neurodevelopmental condition with a global prevalence of 2.5% to 6.7% among adults. Non-pharmacological interventions have demonstrated effectiveness both as standalone treatments and adjuncts to pharmacotherapy in managing adult ADHD. Nevertheless, the comparative efficacy of these interventions, particularly with respect to diverse ADHD-related outcomes and their long-term impacts, remains insufficiently investigated.ObjectiveThis study aims to evaluate and compare the short-term and long-term effects of various non-pharmacological therapies on core ADHD symptoms (inattention, hyperactivity, and impulsivity) and emotional disorders (depression and anxiety) in adults with ADHD and to rank these therapies accordingly.MethodsA systematic search was conducted for relevant randomized controlled trials (RCTs) in the Web of Science, PubMed, Cochrane Library, and EMBASE databases from inception to Sep 2024. Researchers independently screened and extracted data, and the analysis was performed using R version 4.3.2. Cochrane Risk of Bias tool version 2 (ROB2) and Confidence in Network Meta-Analysis (CINeMA) were used to assess the risk of bias and the certainty of the evidence. Standardized mean differences were estimated using network meta-analyses with random effects.ResultsA total of 37 RCTs involving 2,289 participants and 10 non-pharmacological therapies were included. The risk of bias was classified as low in 24.3%, unclear in 27%, and high in 48.6%, while the CINeMA assessment indicated that confidence in the evidence was “very low” or “low” for most of the remaining treatments. Cognitive behavioral therapy (CBT) showed significantly greater effectiveness than the control group/condition in both the short-term (SMD: -4.43, 95%CI: -5.50 to -3.37) and long-term (SMD: -3.61, 95%CI: -4.66 to -2.56) core symptoms. Additionally, CBT shows both short-term and long-term efficacy for depression (SMD: -4.16, 95%CI: -5.51 to -2.81; SMD: -3.89, 95%CI: -5.95 to -1.83) and anxiety (SMD: -2.12, 95%CI: -3.18 to -1.07; SMD: -7.25, 95%CI: -10.57 to -3.94).ConclusionCBT may be the most effective intervention for adults with ADHD and associated emotional disorders, while Mindfulness-based Cognitive Therapy (MC) is recommended as a preferable option for those without comorbidities. Caution is needed in interpreting our results, and high-quality RCTs are urgently required for more reliable insights.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD42024432912.